Pharmacological Interventions to Improve Bone Density in Functional Hypothalamic Amenorrhea: A Systematic Review and Network Meta-Analysis of Randomized Clinical Trials. - Efthymiadis,A; Tsikopoulos,K; Mills,EG; Milne,A; Dhillo,WS; Abbara,A; Comninos,AN (J Clin Endocrinol Metab, 2026)
CONTEXT: Women with functional hypothalamic amenorrhea (FHA) are at high risk of poor bone health. When lifestyle measures fail to restore menses, pharmacological interventions are needed for bone health, but comparative efficacy remains unclear. OBJECTIVE: To compare the efficacy of available pharmacological interventions to improve bone mineral density (BMD), in women with FHA, employing network meta-analysis (NMA). DATA SOURCES: Medline, Embase, Emcare, Cochrane CENTRAL, ISRCTN, and ClinicalTrials.gov were searched up to 20th September 2025. STUDY SELECTION: Eligible randomized-controlled trials evaluated pharmacological interventions for lumbar spine (LS), femoral neck (FN), or total hip (TH) BMD in women with FHA. Two independent reviewers screened titles, abstracts, and texts. DATA EXTRACTION: Two reviewers independently extracted data following PRISMA-NMA guidelines. Outcomes were expressed as standardized mean differences (SMDs) with 95% confidence intervals (CIs) using random-effects NMA. Evidence certainty was assessed with CINeMA. DATA SYNTHESIS: Thirteen RCTs (897 women) were included (LS BMD: n=897; FN BMD: n=370; TH BMD: n=750). Transdermal hormone replacement therapy (HRT) was superior to control (placebo or no intervention) for LS BMD with SMD 0.34 (0.03, 0.64) and FN BMD with SMD 0.57 (0.04, 1.10). Oral HRT and the combined oral contraceptive pill (COCP) showed no significant benefit in any BMD site. Teriparatide was superior to transdermal HRT and COCP for LS BMD with SMDs 1.48 (0.38, 2.59) and 1.75 (0.66, 2.83), but not FN or TH BMD. INTERPRETATION: Transdermal HRT and teriparatide improve LS BMD in women with FHA, with transdermal HRT also improving FN BMD. STUDY REGISTRATION: PROSPERO (CRD42024576872).